Genetic architecture of spatial electrical biomarkers for cardiac arrhythmia and relationship with cardiovascular disease - William J. Young; Jeffrey Haessler; Jan-Walter Benjamins; Linda Repetto; Jie Yao; Aaron Isaacs; Andrew R. Harper; Julia Ramirez; Sophie Garnier; Stefan van Duijvenboden; Antoine R. Baldassari; Maria Pina Concas; et al. (Nature Communications, 2023)
The spatial and frontal QRS-T angles are electrocardiographic (ECG) predictors for arrhythmia. This work used genetic analyses to identify associated loci and pathways, and explore their relationships with other ECG traits and cardiovascular disease.